Amalan tanggungjawab sosial korporat : kajian terhadap proses pembuatan keputusan dan akauntabiliti pelaksanaan rancangan 'Bersamamu' oleh Media Prima Berhad - Julastri, Ibrahim (2017)
The accountability of Corporate Social Responsibility (CSR) implementation in influencing the targeted community and the decision approach of the meaning of CSR should be seen from the practical and theoretical perspectives. The objectives of this study were to know ways of the decision approach in terms of the meaning of CSR and ways the decision-making processes are being made in program ‘BersamaMu’ at Media Prima Berhad. Specifically, there are three main objectives. Firstly, to determine CSR concept in the context of BersamaMu program. Secondly, to determine the decision making process in BersamaMu program. Thirdly, to investigate stimulating factors of rational decision making process of BersamaMu program. A total of 14 respondents who were involved in the production process of the CSR TV program were interviewed for this study. Through thematic analysis, several basic themes were identified and they were categorized into seven main themes. Firstly, CSR concepts in the context of BersamaMu program are poverty, development and participation to the targeted communities. Secondly, there are three types of decision making process, namely consensus-of-round-table, level of decision stages and perspective of stakeholders. Thirdly, situational context of the targeted community stimulated rational decision making process of BersamaMu program. The findings may offer a new approach in understanding the definition and decision making process of CSR through a set of decision-makers’ input and potential decision behaviors.